FTMK Lab And Asset Management System (FLAMS) Asset Management - Ng , Chia Chie (UTeM, 2010)
FTMK Lab and Asset Management System (FLAMS) is a web based system proposed to handle the faculty's lab equipment and managing the assets. This system divided to 5 modules and this document will only discuss on Asset Management module. This module is responsible for handling the entire aspects involve in a lifecycle of an asset during its life time in the faculty. This includes asset registration, inspection, maintenance, relocation and disposal at the end of the lifecycle. It also handles the loan process which includes application, approval and tracking of the loan. Currently, all these process are done manually using paper forms and require face to face interaction to get the process done. Asset Management module provides a computerized and efficient platform to manage the assets. This will reduce the workload of IT manager and asset operator which are responsible for assets. It will also speeds up the process of loan application as the applications are handled systematically. FLAMS are developed using GlassFish as it's server and JavaDB as it's database.